2011
DOI: 10.1063/1.3599047
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of (two-dimensional) molecule-based magnets: [MII(TCNE)(NCMe)2][SbF6] (M = Fe, Mn, Ni)

Abstract: The M-[TCNE] (M = 3d metal; TCNE = tetracyanoethylene) system is one of the most interesting classes of molecule-based magnets, exhibiting a plethora of compositions and structures (inorganic polymer chains, 2D layers, 3D networks, and amorphous solids) with a wide range of magnetic ordering temperatures (up to 400 K). A systematic study of vibrational (both infrared and, for the first time, Raman) properties of the family of new TCNE-based magnets of M(II)(TCNE) (NCMe)(2)[SbF(6)] [M = Mn, Fe, Ni] composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 30 publications
6
21
0
Order By: Relevance
“…These results support the hypothesized stabilization of AFM ordering between localized Mn II -3d and π* [TCNE] − electrons, in accord with the low temperature saturated magnetization studies. 9,35 Thus, our DFT simulations confirm the AFM ground state for both the 2D and 3D Mn- [TCNE] magnets.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results support the hypothesized stabilization of AFM ordering between localized Mn II -3d and π* [TCNE] − electrons, in accord with the low temperature saturated magnetization studies. 9,35 Thus, our DFT simulations confirm the AFM ground state for both the 2D and 3D Mn- [TCNE] magnets.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…9,35 Compound 3D is the recently discovered molecular magnet [Mn II (TCNE) 1.5 ](I 3 ) 0.5 , 11 in which each Mn II ion is octahedrally coordinated to six (NC−) nitrile groups of TCNE anions (Figure 1c). This structure maintains the similar Mn II -μ 4 -[TCNE] − corrugated plane motif, but additionally The experimental structural parameters for the studied 2D and 3D compounds are compared to the ones after geometry optimization in Table S1 (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…This agrees with previously reported experimental data. 11,12 The intralayer, J, and interlayer, K, coupling constants for 2 of structure-type B (M = Mn II , L S = μ 4 -[TCNE] •− , Figure 6. Generalized bonding schemes for M(L S1 )(L S2 ) 1/2 of structure-type C 1 , and M(LS) 3/2 of structure-type C 2 .…”
Section: ■ Mean Field Expressionsmentioning
confidence: 99%
“…8,11,12,16,20 To be selfconsistent with our MF analysis, the same method, namely, the temperature at which the maxima in the frequency independent χ′(T) is used as T c . These values are listed in Table 1. MF theory is useful for predicting trends and for qualitative estimates of exchange constants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Recently, it was shown that monitoring the frequencies of C=C and C≡N bonds by Raman spectroscopy can provide quantitative information about the degree of ligand-tometal charge transfer in [M(TCNE)(NCMe) 2 ]SbF 6 (M = Fe, Mn, Ni) layered magnets. 17 The application of high pressure shortens all TCNE bonds, as well as the metal-to-nitrogen and nitrile group bonds, thus altering total orbital overlap. In addition, it causes the reduction of the interlayer distances affecting the dipole-dipole, inter-layer coupling.…”
Section: Introductionmentioning
confidence: 99%